Persoonallinen ajattelu päättelyssä ja päätöksenteossa - Alho, Tapio (Vaasan yliopisto, 2020)
Tämä tutkimus kohdistuu yksilön kognitiiviseen karttaan tukeutuvaan persoonalliseen ajatteluun ja sen vaikutuksiin päätelmien tuottamisessa ja päätöksenteossa. Tutkijan tavoitteena oli tässä filosofian tutkimuksessa pyrkiä ensinnäkin ymmärtämään ja selittämään, mistä persoonallisessa ajattelussa on faktisesti kyse. Toiseksi tutkija pyrki selvittämään, miten yksilöt tuottavat sen avulla päätöksenteon tueksi päätelmiä itsestään ja ympäristöstään. Kolmanneksi tutkija pyrki selvittämään, miten yksilön kognitiivinen kartta sisältöineen vaikuttaa persoonallisen ajattelun kautta yksilöiden toimeenpanemaan päätöksentekoon. Tutkimustulokset osoittavat, että suurin osa tuottamistamme päätelmistä tuotetaan osin tai kokonaan tiedostamattomasti yksilöllisen subjektiivisuuden välttämättömyyttä noudattaen. Myös päätöksenteossa yksilöllisen subjektiivisuuden välttämättömyys näyttelee merkittävää roolia. Kyse on yksilön tavoiteorientaation (toimiva minä) vaikutuksesta yksilöiden mentaalisiin prosesseihin ja edelleen heidän toimintaansa. Tavoiteorientaation vaikutus ilmenee yksilön haluna menestyä sosiokulttuurisessa ympäristössään ja se implementoi muun muassa byrokraattisena kunnianhimona.

This is research is a Deep Diving to the personal thinking. The main goal of this research was to find out how personal thinking influences individuals conclusions and decision making. It means that the researcher must be able to demonstrate how personal thinking can be comprehensively explained as a cognitive process. The answer to the main question lies in the conclusions. The second important issue to research was how people are developing their self–awareness and the ability to make circumspect decisions. In the research this question is answered with the help of the theoretical framework and empirical data. Empirical data were collected by interviewing 28 public administration representatives and executing a question-naire addressed to one international export company and one public administration unit. 121 respondents from private export (60) company and public sector administration (61) an-swered to the questionnaire. This research is especially aimed at decision makers and those who are interested in their own thinking. It seeks to provide additional information and help them understand the preconditions for their own thinking as part of conclusions and decision-making. The research has been done using a descriptive research methodology. In accordance with the research meth-od, the study focused only on factual knowledge of the subject, i.e. personal thinking in con-clusions and decision-making. This knowledge was aimed to producing a framework of reference and empirical material, each each supporting understanding one another. The main findings of this research were surprising. First of all, individuals draw conclusions to support decision-making, both consciously and unconsciously, and this happens all the time. Research results show too that social pressures, the desire to leave their own fingerprints and the bureaucratic ambition influence decisions made by decision makers. But what struck me most as a researcher is how much metacognitive activity is out of our consciousness. I believe that our knowledge of how many meta-cognitive processes take place outside our conscious-ness is incorrect. Also, our awareness of how strongly individual consciousness implements under individual subjectivity is obviously false a priori. During the research process, I was almost to become a supporter of Cartesian Dualism and sympathizer of my “Homunculus”.
Personal Thinking in reasoning and decision making
Keywords: persoonallinen ajattelu; universaali ajattelu; heuristinen päättely; kognitiivinen vääristymä; tavoiteorientaatio; minä-efekti; tavoiteorientaatio; yksilö; ajattelu; päätöksenteko; päättely; tietoisuus; työmuisti; fi=Tuotantotalous|en=Industrial Management|